Group Guidance with Life Modeling and Behavioral Rehearsal Techniques to Increase Entrepreneurship - Yulistiya Rahmadewi; Uman Suherman; Ilfiandra Ilfiandra (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
Entrepreneurial attitude is an attitude instilled in students through learning about entrepreneurship as well as descriptions of personalities through physical movements and thoughts about entrepreneurship. One of the problems among adolescents is having low entrepreneurial attitude, manifested by being pessimistic and unsure about developing their skills, having weak determination to improve their talents, potential, and interests, lacking the desire to work hard and initiatives to develop their skills, having fear of challenges, and avoiding taking risks. This study aims to encourage students to find freedom, to recognize and acknowledge themselves and their current situations objectively and progressively, to guide themselves, to be able to make decisions, and to actualize themselves more properly. This study used systematic literature review to obtain a higher quality theoretical basis and more detailed, accurate, and complex data.